Harvesting rate of the termite, Drepanotermes tamminensis (Hill) within native woodland and shrubland of the Western Australian wheatbelt - Park, H.; Majer, Jonathan; Hobbs, R.; Bae, T. (1993)
The Western Australian termite, Drepanotermes, tamminensis (Hill), harvests various plant marerials according to biomass availability . The main litter components harvested by this termite in a woodland dominated by Eucalyptus capillosa are bark and leaves of the major tree species, while in shrubland doininated by Allocasuarina campestris, shoots of this species are taken. Harvesting mainly occurs during the autumn (April-May) and spring (September-October) seasons. The commencement and duration of harvesting appears to depend partly on weather conditions, with harvesting taking place at temperatures between 15 and 25 [degrees] C after periods of rain. This species of termite harvests approximately 15.6 [grams per square metre per year] and 3.2 [grams per square metre per year] (dry weight of plant material) in the woocland and shrubland, respectively.